GENERACIÓN DE POLINOMIOS DE SCHUBERT CON COCOA II: GRAFOS RC. - Novoa Ramírez, Jesús Fernando; Departamento de Matemáticas Facultad de Ciencias Pontificia Universidad Javeriana, Bogotá (2004)
The Schubert polynomial associated to a permutation w is encoded by some rc graphs. We develop a computer program for computing Schubert    polynomials using the moves on these graphs.